Epistemologi Bayani, Irfani, dan Burhani Serta Implementasinya Dalam Rekonstruksi Kurikulum PAI - Endy Dharma Pangestu; Haris Riadi; Febby Erika; Nur Azmira (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the integration of Bayani, Burhani, and Irfani epistemologies in the reconstruction of the Islamic Religious Education (PAI) curriculum to make it more relevant to the needs of the 21st century. The Bayani approach, which has been dominant in the curriculum, is considered unable to meet the demands of critical thinking and spiritual strengthening in a balanced manner. The research method uses a literature study by examining classical and contemporary works that discuss Islamic epistemology and its implementation in education. The results show that the three epistemologies have complementary characteristics: Bayani as a normative foundation, Burhani as a strengthener of rationality, and Irfani as a shaper of spiritual depth. The discussion emphasizes the need for integration of the three so that the PAI curriculum produces a holistic, contextual, and character-oriented learning process. In conclusion, curriculum reconstruction based on epistemological integration can improve the quality of PAI learning and shape students who are critical, religious, and adaptive to current developments.